To solve the equation \(-2x + 5 = 6x - 7\), we will first simplify the equation.
Start with the original equation:
\[ -2x + 5 = 6x - 7 \]
Next, we will add \(2x\) to both sides to start isolating \(x\):
\[ 5 = 6x + 2x - 7 \]
This simplifies to:
\[ 5 = 8x - 7 \]
Now, add \(7\) to both sides:
\[ 5 + 7 = 8x \]
So we have:
\[ 12 = 8x \]
Now, divide both sides by \(8\):
\[ x = \frac{12}{8} \]
This simplifies to:
\[ x = \frac{3}{2} \quad \text{or} \quad x = 1.5 \]
Thus, the value of \(x\) is:
\[ \boxed{\frac{3}{2}} \quad \text{or} \quad \boxed{1.5} \]